Creating an islamic boarding school english corpus: corpus metadata, frequently used words, and unique words - Agustina, Yulia; Widodo, Pratomo; Margana, Margana (Intelektual Pustaka Media Utama, 2024)
In the current era, the use of corpora in language teaching is mainly explored in English classes as it has become a trend in education. Hence, this research aimed to identify the corpus metadata, frequently used words, and unique words related to the Islamic boarding school context to be used in the English instructional process. This research employed a mixed method combining quantitative and qualitative data analysis methods. Two English Islamic boarding school books, several articles covering the scope of Islamic boarding school, and students’ speech texts were selected as the data. Then, they were analyzed using the Voyant tool. The finding showed total words of 49,970: 5,417 specific words, 0.108 vocabulary density, and a 12,980-readability index. The finding will be incorporated into instructional resources for developing Islamic boarding school students' general and/or specialized vocabulary. The words, in particular, will provide a foundation for students in constructing Islamic speech texts, delivering speeches, and using English in an Islamic boarding school environment.